Dampak Kemajuan Teknologi Informasi dalam Transformasi Bisnis dan Ekonomi di Indonesia - Supriadin Supriadin; Wardan Wardan; Mohamed Hamdani; Nattapong Srisawatai (Economica Insight, 2025)
Advances in information technology (IT) are driving fundamental changes in business models, market structures, and economic governance in Indonesia. This study aims to analyze the impact of IT on business and economic transformation in Indonesia by 2025, encompassing productivity, business model innovation, employment structure, financial inclusion, and data governance. The methods used include a systematic literature review and secondary data analysis (official statistics, international agency reports, and industry research). The results show that IT adoption accelerates economic growth through process efficiency, expanded market access, and a strengthened digital entrepreneurship ecosystem. However, significant challenges include the digital divide, cybersecurity issues, talent quality, and dependence on global platforms. This study recommends strategies for strengthening digital infrastructure, improving digital literacy and skills, accountable data governance, supporting technology-based MSMEs, and harmonizing regulations to strengthen the competitiveness and resilience of the national digital economy.